Factors affecting banking performance in Pakistan: An empirical investigation - Ahmad, E. W (2022)
Pakistan is one of the economically emerging countries in South Asia. The current trends of Pakistan’s economy are on the path to outshining the former year’s growth rate. The unrelenting performances in the agriculture and services sector and outperformance of the large-scale manufacturing sector. Inflation and the fiscal deficit were confined, whereas revenue growth has surpassed last year’s level. However, Pakistan’s populace is 200 million. However, not many individuals bank with a regulated banking system. The financial system in Pakistan introduced a new phenomenon of the Islamic Banking system that is not a recent idea but has been in the mainstream now for more than a decade. There are several factors internally and externally that stimulate the performance of banks. In this paper, we have tried to investigate how these factors influence the performance of banks in Pakistan. We have used the ROE measure as a dependent variable to evaluate banks' profitability. We have taken the size, age, equity and financial development of the banks. Some external/country-specific factors are also taken into consideration as independent variables. This paper uses panel data from six banks in Pakistan for seven years (2010 to 2017).